A study of the impact of digital financial inclusion on the resilience of the agricultural chain - Gao, Xia; Gao, Ruyun (Frontiers in Sustainable Food Systems, 2024)
Based on the panel data of 30 provinces (except Tibet) from 2011 to 2020, the article examines the impact of digital financial inclusion on the resilience of the agricultural industry chain as well as the mechanism of its action. The results show that: (1) Digital inclusive finance promotes the enhancement of the resilience of the agricultural industry chain, in which the degree of influence on “marketing resilience” and “distribution resilience” is much larger than that on “production resilience,” “processing resilience,” and “product resilience.” The degree of impact on “marketing resilience” and “distribution resilience” is much larger than “production resilience,” “processing resilience,” and “product resilience.” (2) Digital inclusive finance can promote the resilience of the agricultural industry chain through the promotion of agricultural technology innovation and the development of new agricultural business entities. (3) The enhancement of the resilience of the agricultural industry chain is more significant in the eastern region, where the level of digital inclusive finance is high. Based on the results of the study, the article puts forward relevant suggestions in terms of promoting the in-depth integration of digital inclusive finance and the agricultural industry chain, increasing the support for new agricultural business subjects, and strengthening agricultural technological innovation to promote sustainable development of the agricultural industry chain.